Analyzing student performance using SPSS: integrating demographic, socioeconomic, motivational, and support factors - Ahmad, Norhayati; Hamedon, Syasya Nadhirah; Ruslan, Fazlina Ahmat; Johari, Juliana (UiTM Press, 2025)
This study aims to identify key factors influencing the academic performance of students within the College of Engineering. Demographic factors such as age, gender, marital status, socioeconomic factor such as job status, motivational factor such as motivation for continuing studies, and support factor such as academic engagement measured by the frequency of meetings with supervisors were investigated as potential contributors to differences in students academic performance. Data was collected from approximately 130 students in the College of Engineering using a Google spreadsheet. The SPSS statistical tool was employed to analyze these parameters, specifically using Chisquare analysis to determine the association between these factors and the students Cumulative Grade Point Average (CGPA). The results showed that there is a statistically significant association between age and students CGPA. However, the study found no significant association between gender, marital status, job status, motivation for continuing studies, or the frequency of meetings with supervisors and students CGPA. This study contributes to the understanding of factors related to academic achievement in an engineering faculty, providing insights that may help in designing targeted support strategies to enhance student success within the College of Engineering.